Plant Hormones Biosynthesis, Signal Transduction, Action! - Davies, Peter J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Plant hormones play a crucial role in controlling the way in which plants grow and develop. While metabolism provides the power and building blocks for plant life, it is the hormones that regulate the speed of growth of the individual parts and integrate them to produce the form that we recognize as a plant. This book is a description of these natural chemicals: how they are synthesized and metabolized, how they act at both the organismal and molecular levels, how we measure them, a description of some of the roles they play in regulating plant growth and development, and the prospects for the genetic engineering of hormone levels or responses in crop plants. This is an updated revision of the third edition of the highly acclaimed text. Thirty-three chapters, including two totally new chapters plus four chapter updates, written by a group of fifty-five international experts, provide the latest information on Plant Hormones, particularly with reference to such new topics as signal transduction, brassinosteroids, responses to disease, and expansins. The book is not a conference proceedings but a selected collection of carefully integrated and illustrated reviews describing our knowledge of plant hormones and the experimental work that is the foundation of this information. The Revised 3rd Edition adds important information that has emerged since the original publication of the 3rd edition. This includes information on the receptors for auxin, gibberellin, abscisic acid and jasmonates, in addition to new chapters on strigolactones, the branching hormones, and florigen, the flowering hormone.
The Plant Hormones: Their Nature, Occurrence, and Functions -- Regulatory Factors in Hormone Action: Level, Location and Signal Transduction -- Hormone Biosynthesis, Metabolism and its Regulation -- Auxin Biosynthesis and Metabolism -- Gibberellin Biosynthesis and Inactivation -- Cytokinin Biosynthesis and Metabolism -- Ethylene Biosynthesis -- Abscisic Acid Biosynthesis and Metabolism -- Brassinosteroid Biosynthesis and Metabolism -- Regulation of Gibberellin and Brassinosteroid Biosynthesis by Genetic, Environmental and Hormonal Factors -- The Final Action of Hormones -- Auxin and Cell Elongation -- Gibberellin Action in Germinated Cereal Grains -- Cytokinin Regulation of the Cell Division Cycle -- Expansins as Agents in Hormone Action -- Hormone Signal Transduction -- Auxin Signal Transduction -- Gibberellin Signal Transduction in Stem Elongation & Leaf Growth -- Cytokinin Signal Transduction -- Ethylene Responses in Seedling Growth and Development -- Ethylene Signal Transduction in Fruits and Flowers -- Abscisic Acid Signal Transduction in Stomatal Responses -- Brassinosteroid Signal Transduction and Action -- The Functioning of Hormones in Plant Growth and Development -- The Transport of Auxins -- The Induction of Vascular Tissues by Auxin -- Hormones and the Regulation of Water Balance -- The Role of Hormones during Seed Development and Germination -- Hormonal and Daylength Control of Potato Tuberization -- The Hormonal Regulation of Senescence -- Genetic and Transgenic Approaches to Improving Crop Performance -- The Roles of Hormones in Defense Against Insects and Disease -- Jasmonates -- Salicylic Acid -- Peptide Hormones for Defense, Growth, Development and Reproduction -- Hormone Analysis -- Methods of Plant Hormone Analysis.
Keywords: Plant science; Botany; Plant Sciences